2022
DOI: 10.15252/embr.202152775
|View full text |Cite
|
Sign up to set email alerts
|

Male infertility‐associated Ccdc108 regulates multiciliogenesis via the intraflagellar transport machinery

Abstract: Motile cilia on the cell surface generate movement and directional fluid flow that is crucial for various biological processes. Dysfunction of these cilia causes human diseases such as sinopulmonary disease and infertility. Here, we show that Ccdc108, a protein linked to male infertility, has an evolutionarily conserved requirement in motile multiciliation. Using Xenopus laevis embryos, Ccdc108 is shown to be required for the migration and docking of basal bodies to the apical membrane in epidermal multiciliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…Recently, a novel subfamily comprising MOSPD1 and MOSPD3 was characterized; these proteins have an MSP domain that recognizes FFNT (two phenylalanines in a neutral tract) motifs ( Cabukusta et al, 2020 ). Lastly, the sixth family member named CFAP65 (Cilia- and flagella-associated protein 65) is involved in ciliogenesis ( Zhao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel subfamily comprising MOSPD1 and MOSPD3 was characterized; these proteins have an MSP domain that recognizes FFNT (two phenylalanines in a neutral tract) motifs ( Cabukusta et al, 2020 ). Lastly, the sixth family member named CFAP65 (Cilia- and flagella-associated protein 65) is involved in ciliogenesis ( Zhao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…6h, i ), supporting specificity of the phenotypic rescues. We note that unlike hyls- 1 and dlg5 , both ccdc108 and gas2l2 directly regulate the CBF 43 , 45 , suggesting a common mode of action that can be modulated by Wnt but whose precise mechanism remains to be established. Taken together, these results support that i) the Wnt ┫Pp1 signaling axis increases CBF, ii) that this feature is conserved, and iii) that activating the Wnt ┫Pp1 signaling axis improves ciliary performance in certain pathological contexts (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The evolutionary conservation of a CBF-stimulatory role prompted us to explore if Wnt ┫Pp1 signaling could be beneficial in human ciliopathies. Therefore, we injected previously characterized morpholinos that recapitulate ciliopathy- and fertility-associated diseases in Xenopus MCCs, including ccdc108 (male infertility), dlg5 (multi-organ congenital defects), gas2l2 (primary ciliary dyskinesia), and hyls-1 (perinatal hydrolethalus) 43 46 . Ccdc108- , gas2l2- and hyls-1 morpholinos induced not only mucociliary deficiency but also mild axial defects (reduced head, increased belly) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, immunofluorescence staining of CFAP65 has been visualized in the acrosome and midpiece of spermatozoa, indicating its potential function in acrosome biogenesis and flagellar assembly, which has been demonstrated in subsequent animal experiments ( Wang et al, 2019 ). A mouse model has indicated that Cfap65 plays an important role in sperm head shaping, acrosome biogenesis and MS assembly ( Wang W. et al, 2021 ), while a previous study in Xenopus laevis embryos, Cfap65 has been indicated to cooperate with IFT-B complex components and regulate multiciliogenesis via an IFT mechanism ( Zhao et al, 2022 ). CFAP70 is another MMAF-related gene that encodes a protein with unclear functions ( Beurois et al, 2019 ).…”
Section: Pathogenic Genes and Their Function Inspermatogenesismentioning
confidence: 99%
“…To date, there is no report on a successful ICSI outcome for patients harboring CFAP65 mutations. A recent study has reported that CFAP65 localizes to centrioles in the cilium in Xenopus and plays a key role in basal body migration during multiciliogenesis ( Zhao et al, 2022 ). CFAP65 deficiency in mice results in abnormalities in sperm head shaping and acrosome biogenesis, which is crucial to subsequent embryonic development after sperm injection ( Wang W. et al, 2021 ).…”
Section: Icsi Outcome Of Mmaf Patientsmentioning
confidence: 99%